Cervical Epidural Anaesthesia with Ropivacaine for Modified Radical Mastectomy - Kulkarni, K; Namazi, IJ; Deshpande, S; Goel, R (Kathmandu University Medical Journal, 2015)
Background Cervical epidural anaesthesia (CEA) using local anesthetics (LA) is a well established technique for the surgeries in the neck, chest and upper arms. Recently ropivacaine is introduced with better safety profile. Objectives The aim was to observe the safety of Cervical epidural anaesthesia as an anaesthetic technique and to compare the efficacy of epidural 0.25% bupivacaine with 0.375% ropivacaine for radical mastectomies. Methods A double blind study was conducted on 40 ASA grade I / II females who received CEA with 10 ml of 0.25% of bupivacaine +25μg of fentanyl in group B (n=20) and 10 ml of 0.375% of ropivacaine +25μg of fentanyl in group R (n=20) epidurally. Assessment of the block, vital monitoring and complications noted. Results No significant differences observed in the onset of sensory block (5.05min and 5.4min in group B and R respectively, P>0.05).The mean motor blockade score, time to achieve complete blockade and time to grade I motor recovery was significantly longer in group B (2.3, 22.5 and 79.5 minutes respectively) as compared to group R (1.5, 18.3 and 66.3 minutes respectively, P<0.05). Respiratory distress developed in two patients of group B that required general anaesthesia (GA) with intubation. Conclusion Use of 0.37% ropivacaine is safer than 0.25% bupivacaine for CEA for radical mastectomy. It provides good surgical anaesthesia with lesser degree of motor blockade and the respiratory effects. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12487 Kathmandu University Medical Journal Vol.11(2) 2013: 126-131